Role of intragrain oxygen diffusion in polycrystalline tin oxide conductivity - Aldao, Celso Manuel (2011)
Resistivity transients of tin oxide films at step isothermal changes in oxygen pressure are investigated. It is expected that, after exposing the samples to oxygen, the resistivity would increase monotonically as barriers become higher to finally reach a plateau at steady state. Here we present experimental results showing a nonmonotonic resistivity transient response that cannot be explained by only considering changes in the Schottky barrier heights. We provide an explanation based on the effects of intragrain oxygen diffusion that accounts for the observed main features of conduction in this polycrystalline material. Oxygen diffuses into the grains annihilating vacancies; the donor concentration is then reduced affecting the sample conductivity.